Antiatherosclerotic Potential of Clopidogrel: Antioxidant and Anti-Inflammatory Approaches. (26th December 2013) - Hadi, Najah R.; Mohammad, Bassim I.; Ajeena, Ihsan M.; Sahib, Hussam H.
Abstract : Background . Atherosclerosis is characterized by endothelial dysfunction, vascular inflammation, and the buildup of lipids, cholesterol, calcium, and cellular debris within the intima of the walls of large and medium size arteries. Objective . To evaluate the effect of clopidogrel on atherosclerosis progression. Materials and Methods . A total of 28 local domestic rabbits were assigned to four groups: normal control, atherogenic control, vehicle control, and clopidogrel treated. Serum triglycerides, total cholesterol, HDL-C, plasma high sensitive C-reactive protein (hsCRP), plasma malondialdehyde (MDA), and plasma reduced glutathione (GSH) were measured at the end of the experiment. Immunohistochemical of aortic atherosclerotic changes were also performed. Results . There was no statistically significant difference between atherogenic control group and vehicle group. Levels of lipid profile, atherogenic index, hsCRP, and MDA are increased while GSH levels were decreased in animals on atherogenic diet. Immunohistochemical analysis showed that aortic expressions of VCAM-1, MCP-1, TNF- α, and IL-17A were significantly increased in atherogenic control group. Histopathologic finding showed that animals on atherogenic diet have significant atherosclerotic lesion. Compared to atherogenic control group clopidogrel do not have significant effect on lipid profile. Clopidogrel significantly reduces hsCRP and MDA levels and increases GSH level. Furthermore, clopidogrel treatment significantly reduced aortic expressions parameters and the histopathologic examination of the aortic arch showed a significant reduction of atherosclerotic lesion. Conclusions . This study outlines how clopidogrel reduces lipid peroxidation, systemic inflammation, and aortic expression of inflammatory markers and hence reduces the progression of atherosclerosis.